An intelligent multi-agent memory assistant - Costa, Ângelo (2011)
World population is ageing and increasingly scarce resources are required to cover the needs of everyone adequately. Medical conditions, especially memory problems, restrict the daily life of a broad slice of the elderly population, affect their independence. To prevent this, providing the right care and assistance while having in mind the costs implicated is essential. One possible path is to work with resources that we already have today and create innovative solutions to achieve the required level of support. There are not many solution either technological or not to prevent memory loss. In this work we present a possible solution aimed at restoring or maintaining the independence of elderly people, through the use of so-called Memory Assistants. We thus present an Intelligent Multi-Agent Memory Assistant designed to help people with memory problems remember their events and activities. The implementation of an event manager, free time manger, medication remainder and a sensory system, to manage and monitor the user, we aim to improve their quality of life and increase their independence.